Design and Implementation of a Website-Based Information System at SMK TI XYZ - Miftahul Huda; Nanang Pradita; Rahmat Hidayat (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2023)
The website is one of the information systems that must exist in the education organization. The website is designed and built to be one of the means of delivering practical information and as a means of promotion for schools. This research uses the Waterfall method, which is included in the SDLC (Software Development Life Cycle) method category. The SDLC method refers to developing software systems using models based on well-tested methods. The waterfall method is generally used in software development, which begins with analyzing, designing, coding, testing, and maintenance. The result of designing the SMK website is implementing a website all users can access to get the information. In addition, the website is expected to help schools as an effective promotional media.